2016
DOI: 10.1007/s11010-016-2875-y
|View full text |Cite
|
Sign up to set email alerts
|

SH003 enhances paclitaxel chemosensitivity in MCF-7/PAX breast cancer cells through inhibition of MDR1 activity

Abstract: Paclitaxel is an anti-cancer drug for treating cancer, but paclitaxel resistance is reported in cancer cells. Multidrug resistance (MDR) is related with the epithelial-to-mesenchymal transition (EMT) mechanism, which plays a key role in cancer metastasis. Moreover, EMT mechanism is connected to tamoxifen resistance in breast cancer cells. Consequently, oncologists are interested in finding new MDR1 inhibitors originating from herbal medicines to have less side-effect. Here, we investigated an inhibition effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…In line with this, both untreated and PTX-treated PTX-res MCF-7 cells showed a significant MDR1/ABCB1 protein expression profile compared to wt cells [ 26 ] ( Figure 1 B). Similar to our findings, PTX-res MCF-7 cells showed increased MDR1 activation and protein expression levels linked with the EMT signaling pathway [ 27 ]. The wt MCF-7 cells showed an epithelial cell profile with their apicobasal polarity formation and close contact with each other.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this, both untreated and PTX-treated PTX-res MCF-7 cells showed a significant MDR1/ABCB1 protein expression profile compared to wt cells [ 26 ] ( Figure 1 B). Similar to our findings, PTX-res MCF-7 cells showed increased MDR1 activation and protein expression levels linked with the EMT signaling pathway [ 27 ]. The wt MCF-7 cells showed an epithelial cell profile with their apicobasal polarity formation and close contact with each other.…”
Section: Discussionsupporting
confidence: 91%
“…The chemotherapy response in various cancer patients is frequently compromised by drug insensitivity, which eventually leads to treatment failure [33, 34]. Numerous genes associated with the drug sensitivity of chemotherapy have been identified [35].…”
Section: Discussionmentioning
confidence: 99%
“…The present study administered SH003 alone; however, the results of experimental studies on the efficacy of the combined treatment of SH003 and anticancer drugs including doxorubicin and paclitaxel have been reported. 23,24 We are also interested in combination therapy and have received investigational new drug approval from the Ministry of Food and Drug Safety (MFDS) for a Phase 1/2 clinical trial of combination therapy. Several preclinical studies have shown that SH003 has an anticancer effect on breast cancer.…”
Section: Discussionmentioning
confidence: 99%